Karakteristik dan Motivasi Wisatawan yang Berkunjung di Pantai Kelan, Badung, Bali - Septiani, Ketut Dewi; Adikampana, I Made (JURNAL DESTINASI PARIWISATA, 2023)
Tourists have different characteristics and motivations in visiting travel destinations because each individual has differences in interests, preferences, and needs. This study aims to determine the characteristics of tourists in terms of demographic aspects, and determine tourist motivation in terms of intrinsic and extrinsic aspects at Kelan Beach. This study used a quantitative and qualitative descriptive approach, primary data sources, observation and questionnaires data collection. The sample taken was 50 respondents with the purposive sampling method. The data analysis technique used is descriptive statistics. The results of this study prove that the tourist characteristics at Kelan Beach based on domicile are dominated by visitors from Tuban (54%), based on gender are women (28%), based on age are 26-34 years (34%), based on occupation are private sector employees (38%), and based on income are the range of IDR 3,000,000–IDR 5,000,000 per month (44%). Balance and relaxation (38%) are the most influential intrinsic motivational factors for tourists to visit Kelan Beach, while being with friends, partners or family (50%) are the most influential extrinsic motivational factor. Kelan Beach tourism managers are expected to consider the results of this study to be able to pay attention to the characteristics of tourists, adjust facilities and services according to tourist motivations in order to provide a relevant and satisfying experience for visitors. Keywords: Tourist Characteristics, Tourist Motivation, Tourist Attraction, Kelan Beach